KAJIAN MASTER PLAN PEMBANGUNAN EKONOMI KABUPATEN PINRANG - Nasriah Akil (AkMen JURNAL ILMIAH, 2012)
Regional economic development is largely determined by the level of economic activity based on economic sectors that encourages an increase in Gross Domestic Product and the strengthening of regional economic structure, Optimization of the economic potential of the region is highly dependent on the level land ready kesesuaiaan subsectors in each sub-sector is the basis sectors that have a commodity that is considered superior in every sub-district that was dilahan either wet or on dry land, the potential for regional economic development is not only supported by the agricultural sector which is considered the base, however, supported by the development sector as a basis for encouraging the economic activities based districts, Strarategi and regional economic development policy is supported by a strategic program that will be described at the level SKPD and other entities related to the economic development of the region.